As estratégias de negação variantes no inglês falado: uma comparação com o português - Silva, Edilson dos Santos (2009)
The general aim of this work is to verify the occurence of variant forms of negation in spoken English with the purpose of making a comparative study between the English and the Portuguese languages. As for Portuguese, we used as a matter of reference a study already made on negation. As for English, we analized a corpus of the North American English variant organized by a university in the United States. This study is based on the North American Functional Linguistics theoretical perspective, which considers relevant the study of language used in real situations of communicative interaction. The data analisys proved that there is at least one form of negative variant in spoken English which is not allowed by prescriptive grammar. This phenomenon turns out to be similar to Portuguese, which includes three variant strategies. According to the data obtained, it was possible to verify that the variant strategy used in English, from a contrastive point of view, corresponds to a negative strategy ruled by Portuguese prescriptive grammar. Finally, we discussed about the different conceptions of language, grammar and teaching, giving suggestions to colaborate to a productive and reflexive teaching of first or second language